The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/adom.201900916
|View full text |Cite
|
Sign up to set email alerts
|

Mg2+‐Alloyed All‐Inorganic Halide Perovskites for White Light‐Emitting Diodes by 3D‐Printing Method

Abstract: All‐inorganic halide perovskites (CsPbX3, X = Cl−, Br−, and I−) are brought to the forefront of research focus in the field of modern lighting technology. However, due to the toxic element (Pb2+), environmentally friendly white‐light emissions are difficult to achieve, thus limiting their practical applications. Herein, high‐quality Mg2+‐alloyed CsPb1−x Mgx X3 (up to 20%) nanocrystals (NCs) are synthesized. The structural and optical properties are investigated. The application of these NCs in white‐light‐emit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 57 publications
1
41
0
Order By: Relevance
“…The increased doping concentration also leads to peak broadening and splitting at 30.7°, which indicates a symmetry-lowering tilt and distortion of the [BX 6 ] 4− octahedron. [17,29] Such distortions are also predicted by our first principles calculations, but they are below 1.5°. It has been reported that doping can induce structural evolution, especially when the size mismatch between the dopant and substituted atoms is large, [29,31,36] but the calculated small distortion here indicates the lattice contraction and octahedral tilting are not strong enough to induce a distinct structural change.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The increased doping concentration also leads to peak broadening and splitting at 30.7°, which indicates a symmetry-lowering tilt and distortion of the [BX 6 ] 4− octahedron. [17,29] Such distortions are also predicted by our first principles calculations, but they are below 1.5°. It has been reported that doping can induce structural evolution, especially when the size mismatch between the dopant and substituted atoms is large, [29,31,36] but the calculated small distortion here indicates the lattice contraction and octahedral tilting are not strong enough to induce a distinct structural change.…”
Section: Resultssupporting
confidence: 83%
“…[13] B-site cations also play a critical role in determining the electronic band structure of perovskites and consequently their emission properties. Recent studies have demonstrated successful B-site doping using alkaline-earth metal ions (Mg 2+ , Ba 2+ , Sr 2+ ), [14][15][16][17] transition metal ions (Cu 2+ , Cd 2+ , Ag + , Zn 2+ ), [18][19][20][21] metalloid ions (Sn 2+ , Bi 3+ ), [22][23][24] and lanthanide ions (Ce 3+ , Tb 3+ , Yb 3+ ). [25][26][27] Despite these advantages, dopants may also lead to negative effects on the properties of NCs.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the toxicity problem, more endeavors should be taken in the development of heavy-metal-free impurity-doped nanocrystal LEDs [ 353 , 354 , 355 ], otherwise it will be difficult to enter the mainstream display, lighting, and signaling markets. For the lifetime issue, no impurity-doped nanocrystal LEDs with satisfactory operational stability have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, by blending blue CsPbBrxCl3-x QDs with orange polymer of poly[2-methoxy-5-(2-ethylhexyloxy)1,4-phenylenevinylene] (MEH:PPV) with the ratio of 9 : 1, a single-EML white LED with CIE chromaticity coordinates of (0.33, 0.34) was demonstrated ( Figure 5.3). [179] Other additional emitters, like rare-earth ion Sm 3+ , [180] alkali metal Mg 2+ , [181] also show good compatibilities with perovskites. Adapted from reference.…”
Section: Perovskite-based Hybrid White Ledsmentioning
confidence: 99%